The Implementation of Repetition and Chain Drill at Akademi Maritim Nusantara Cilacap - Dhion Meitreya Vidhiasi (CV. Tripe Konsultan, 2022)
The act of communicating using English is still an obstacle for students, especially for countries that make English as a foreign language. English conversation must be mastered fluently by students of Akademi Maritim Nusantara Cilacap, especially the Nautical Sciences Study Program. This becomes an obligation because as seafarers, graduates will definitely have to deal with many people from other countries. Learning English conversation by imitation is seen as still relevant when viewed from the position of English as a foreign language in Indonesia. This study aims to see the impact of applying repetition and chain drill methods in learning Maritime English at the Akademi Maritim Nusantara Cilacap. The Repetition and Chain Drill methods are part of a language teaching method called the Audio-Lingual Method. Both methods are implemented in one Nautical Science class which contains 33 students. With the help of 33 Nautical program students, the research was done utilizing the Classroom Action Research approach. Three study steps yielded the necessary data. Researchers assess each student’s fluency and pronunciation in various ways. The results showed that there was an increase in the average value between stages. It also proves that learning with repetition and chain drill methods helps students start English conversation.